The impact of functional load and cumulative errors on listeners' judgments of comprehensibility and accentedness. (November 2022) - Alnafisah, Mutleb; Goodale, Erik; Rehman, Ivana; Levis, John; Kochem, Tim
Abstract: The Functional Load (FL) principle, in which the gravity of errors in segmentals can be estimated by how frequently two phonemes distinguish words in a language, is crucial to intelligibility-based instruction of Second Language (L2) pronunciation (Derwing & Munro, 2015; Levis, 2018). Despite its attractiveness, the evidence for broad applicability of the principle remains modest, and the cumulative effect of errors is understudied. In this paper, we investigate the impact of FL and error frequency on judgments of comprehensibility and accentedness. This study employed a database of read-aloud sentences with one, two, three, and four high and low FL errors as well as sentences with both high and low FL errors. Thirty-one native speakers of English rated the comprehensibility and accentedness of the sentences. High FL errors were associated with greater loss of comprehensibility and judgments of higher accentedness than low FL errors. Utterances with low FL errors received significantly lower comprehensibility ratings as errors increased beyond two. However, ratings of comprehensibility for high FL errors deteriorated beyond three errors. For accentedness judgments, higher error frequency affected high FL errors only. Overall, the results confirm earlier findings for the usefulness of functional load as a metric for L2 pronunciation teaching, but raise questions about whether findings for extremes on the 10-point FL hierarchy (Brown, 1988) reflect error gravity findings for the middle of the hierarchy.